Hepatitis C Virus—Core Antigen: Implications in Diagnostic, Treatment Monitoring and Clinical Outcomes - Duong Hoang Huy Le; Sitthichai Kanokudom; Ha Minh Nguyen; Ritthideach Yorsaeng; Sittisak Honsawek; Sompong Vongpunsawad; Yong Poovorawan (Viruses)
The hepatitis C virus (HCV) infection, a global health concern, can lead to chronic liver disease. The HCV core antigen (HCVcAg), a viral protein essential for replication, offers a cost-effective alternative to HCV RNA testing, particularly in resource-limited settings. This review explores the significance of HCVcAg, a key protein in the hepatitis C virus, examining its structure, function, and role in the viral life cycle. It also evaluates its clinical use in diagnosis and treatment monitoring, comparing its performance to the standard HCV RNA assay using data from PubMed and Google Scholar. HCVcAg assays show high pooled sensitivity (93.5%) and pooled specificity (99.2%) compared to HCV RNA assays, correlating closely (r = 0.87) with HCV RNA levels. Hence, HCVcAg testing offers a cost-effective way to diagnose active HCV infections and monitor treatment, especially in resource-limited settings, but its sensitivity can vary and standardization is needed. HCVcAg also predicts liver disease progression and assesses liver damage risk, aiding patient management. It helps to identify patients at risk for fibrosis or carcinoma, making it vital in hepatitis C care. HCVcAg testing can expand access to HCV care, simplify management, and contribute to global elimination strategies, especially in low- and middle-income countries.